THE EXISTENCE OF REGIONAL REGULATION DEALING WITH SOCIAL RESPONSIBILITY BASED ON THE ESTABLISHMENT OF REGULATION - Eka NAM Sihombing , Eddy Purnama , Budiman Ginting , Faisal Akbar Nasution (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The application of corporate social responsibility is becoming increasingly important, where social responsibility is the company commitment or the business world to contribute the sustainable economic development by paying attention to corporate social responsibility and emphasizing the balance between attention to economic, social, and environmental aspects. However, there is a problem in its application. One of them is a legal instrument or form of legislation that is used related to the regulation of corporate social responsibility. Where, in many areas set in the form of regional regulations. This will then be seen in this paper how the enactment of regional regulations on social responsibility is seen from the principle of establishing good legislation. Based on a review of regional regulation on social responsibility, it is found that the issued of regional regulation dealing with corporate social responsibility violates the principle of establishing laws and regulation, namely the principle of conformity between types and material content. Based on Article 74 paragraph (4) of Law Number 40 Year 2007 dealing with Limited Liability Companies, the regulation on corporate social and environmental responsibility is regulated by Government Regulation, not by regional regulation.